The worldwide trend in diabetes awareness, treatment, and control from 1985 to 2022: a systematic review and meta-analysis of 233 population-representative studies - Ehsan Shahrestanaki; Ehsan Shahrestanaki; Nami Mohammadian Khonsari; Ehsan Seif; Fereshteh Baygi; Hanieh-Sadat Ejtahed; Hanieh-Sadat Ejtahed; Ali Sheidaei; Shirin Djalalinia; Dianna J. Magliano; Dianna J. Magliano; Mostafa Qorbani; et al. (Frontiers Media S.A., 2024)
BackgroundWith the rapid increase in the prevalence of DM, studies on the awareness, treatment, and control of this condition are essential. Therefore, this study aimed to review the literature and pool the awareness, treatment, and control of diabetes at the global, regional, and national levels.MethodsIn this systematic review and meta-analysis, several databases, including MEDLINE/PubMed, Institute of Scientific Information (ISI), Scopus, and Google Scholar, were searched using appropriate keywords up to June 2022. Observational studies investigating the awareness, treatment, and control of glucose levels among diabetic individuals were included. Awareness, treatment, and control were defined as the proportion of participants who were aware of their diabetes condition, treated pharmacologically, and achieved adequate glucose control, respectively. Two investigators independently conducted the study selection, data extraction, and quality assessment. Heterogeneity among studies was calculated using Chi-square, and a random-effect meta-analysis was used to pool the rates.ResultsA total of 233 studies published between 1985 and 2022 met the inclusion criteria. The included studies had a combined population of 12,537,968. The pooled awareness of DM was 60% (95%CI: 56-63) and ranged from 41% (25-57) in low-income countries to 68% (64-72) in high-income countries, with no significant trend observed over the assessed periods at the global level. The pooled treatment of DM globally was 45% (42-48) and varied from 37% (31-43) in lower-middle-income countries to 53% (47-59) in high-income countries, showing variation over the examined time period. Before 2000, the proportion of adequate DM control was 16% (12-20), which significantly improved and reached 22% (19-25) after 2010. The pooled awareness, treatment, and control of DM were higher in females, high-income countries, and urban areas compared to males, upper and lower-middle-income countries, and rural areas, respectively. The older adults population had higher awareness and treatment rates than the adult population, but their DM control did not differ significantly.ConclusionDespite the high level of awareness and treatment among the diabetic population, treatment success (control) is considerably low, particularly in low-income countries and rural areas. It is crucial to improve awareness, treatment, and control by strengthening the primary care system in all countries.